Enzymatic flow injection analysis of coprostanol in non-aqueous media - Piñeiro Avila, Gerardo; Salvador, Amparo; De la Guardia, Miguel (Ciencia, 1970)
An alternative method has been developed for the spectrophotometric determination of coprostanol in sediments, based on its extraction with chloroform-methanol(2+1 v/v) and enzymatic analysis in pH 7.0 buffer saturated toluene, using a bienzymic reactor prepared with 1 mg cholesterol oxidase (23 IU) and 1 mg horseradish peroxidase (220 PU) both noncovalently immobilised on controlled pore glass beads. The method allow us to determine coprostanol in a dynamic range from 2.2xl0-4 M to 9x10-4 M , measuring the absorbance at 458 nm of the oxidized form of p-anisidine. The relationship between absorbance (A) and coprostanol concentration (C) expressed in mol.L-1 was A = (0.0059 Ó 0.0005) + (17 Ó 1) (C) with a r2 = 0.998 and it was obtained a limit of detection of 7x10-6 M in the best experimental conditions. Recovery studies carried out on water and beach sediments, at concentration levels from 0.1 to 0.25 mg.g1, provided values from 96 to 112%.